Leucorrhoea Relief: Harnessing the Power of Ayurveda for Natural Healing - A Case Report - Bhagyashri V. Chaudhari; Nishigandha A. Kubade; Ishwari S. Gaikwad; Sughosh R. Bhende (Journal of Pharmacy and Bioallied Sciences)
Shwetapradar, commonly known as leucorrhea, is a gynecological condition characterized by abnormal vaginal discharge. While it is normal to a certain extent, its pathological manifestation can become severe, often overshadowing the primary cause and prompting patients to seek treatment for this specific symptom. Traditional Ayurvedic approaches to managing Swetapradara (leucorrhea) include addressing the root causes, adopting the Kapha shamak (kapha mitigating) diet, and employing specific procedures such as vaginal suppositories, douches, and fumigation, alongside symptomatic treatment. This case report presents the successful management of a 32-year-old female suffering from chronic leucorrhea. The patient underwent effective treatment through Shamana chikitsa, which involved the administration of a therapeutic combination along with Sthanik Chikitsa (local treatment) of Yoni Dhavana (vaginal douche). This comprehensive therapeutic approach aimed at addressing the patient’s condition, reflects a well-rounded strategy that leverages the synergistic benefits of these specific medicinal elements.